Transaksionalisme Amerika Serikat dalam Normalisasi Hubungan Maroko-Israel - Ilham, Muhammad; Paksi, Arie Kusuma (State Islamic Institute of Kudus (IAIN Kudus), 2022)
AbstractIn 2020, Morocco became the fourth Arab state that normalized ties with Israel in that year. The normalization deal is brokered by the US under Trump administration. This article aims to explain the reason behind Morocco’s decision to normalized ties with Israel. This article utilizes conceptual framework of transactionalism as the tool of analysis with qualitative-explanative research methods. The findings of this article indicate that Morocco was willing to normalize ties with Israel in exchange for US recognition of Morocco sovereignty over Western Sahara. Moreover, the US was giving additional incentives in the form of financial investment and military equipment sale. The US recognition of Morocco sovereignty over Western Sahara is problematic because it is contrary to the UN resolution. However, US success in brokering the normalization deal has improved Trump’s image. The Moroccan government also managed to gain popularity due to recognition over Western Sahara.